Oscillatory Failure Case detection in flight control systems via wavelets decomposition. (September 2022) - Forouzanfar, M.; Safaeipour, H.; Casavola, A.
Abstract: A fault detection design is proposed for addressing the Oscillatory Failure Case (OFC) detection problem, introduced in the joint Airbus-Stellenbosch university aerospace industrial-benchmark competition called at the IFAC 2020 World Congress 1 . The detection scheme is comprised of an output estimator, a wavelet decomposition and an energy-based denoising method, and the residual evaluation unit. The detection problem of wide frequency range OFCs is also addressed. According to the achieved simulation results, the proposed fault detection method is able to satisfy the competition prescriptions in the frequency range [1 10] Hz for those OFC's having an amplitude greater than 2.3 mm for OFCs at rod position sensor, or 1.4 mA for OFCs at servo input current, regardless of disturbances level, uncertainties and load factor control input. In other cases, faults are detected slightly after the prescribed detection limit, with some interesting exceptions. Graphical abstract: Highlights: An oscillatory failure case detection scheme is presented to be used in the flight control systems. A general detection solution using discrete wavelet decomposition is provided. OFCs with amplitude beyond 2.3 mm at the rod sensor and 1.9 mA in the servo input are detectable.